Tales from the crypt and coral reef: the successes and challenges of identifying new herpesviruses using metagenomics - Houldcroft, Charlotte J.; Breuer, Judith (Frontiers in Microbiology, 2015)
Herpesviruses are ubiquitous double-stranded DNA viruses infecting many animals, with the capacity to cause disease in both immunocompetent and immunocompromised hosts. Different herpesviruses have different cell tropisms, and have been detected in a diverse range of tissues and sample types. Metagenomics – encompassing viromics – analyses the nucleic acid of a tissue or other sample in an unbiased manner, making few or no prior assumptions about which viruses may be present in a sample. This approach has successfully discovered a number of novel herpesviruses. Furthermore, metagenomic analysis can identify herpesviruses with high degrees of sequence divergence from known herpesviruses and does not rely upon culturing large quantities of viral material. Metagenomics has had success in two areas of herpesvirus sequencing: firstly, the discovery of novel exogenous and endogenous herpesviruses in primates, bats and cnidarians; and secondly, in characterising large areas of the genomes of herpesviruses previously only known from small fragments, revealing unexpected diversity. This review will discuss the successes and challenges of using metagenomics to identify novel herpesviruses, and future directions within the field.